High Sensitivity C-Reactive Protein as Atherogenic Marker Among Type 2 Diabetes - Abdelmarouf H. Mohieldein; Marghoob Hasan; Mahmoud I. El-Habiby (European Scientific Journal, ESJ, 2017)
Background: People with type 2 diabetes are threefold affected by cardiovascular disease (CVD) compared with non-diabetics. Many studies reported the absence of traditional CVD risk factors in a substantial portion of individuals experiencing clinical vascular events. Novel risk markers for CVD are often said to add independent predictive value for risk prediction. Objective: In the present study we evaluated different CVD risk factors based on highsensitivity C-reactive (hs- CRP) protein quartiles among diabetics and nondiabetics population. Methods: In this population- based cross- sectional study, we recruited a total of onehundred and nine participants (64 type 2 diabetics and 45 healthy controls). Venous blood sample collected from each subject. Body weight and height were measured and body mass index (BMI) was calculated. Biochemical analytes were measured according to standard procedures. Data analyzed using SPSS software. Results: Mean serum hs-CRP levels were significantly higher among diabetics (2.3 mg/l) compared to controls (1.8 mg/l; P = 0.019). Moreover, the 3rd & 4th quartiles of hs-CRP were characterized by more frequency of diabetes as well as hypertension. The percent of participants with diabetes or hypertension seemed positively related to hs CRP concentrations. Lipid profile analysis revealed the highest levels of LDL-C and Apo B in 4th quartile hs-CRP. In addition, participants in the 4th quartile hs-CRP were characterized by the highest age, BMI, plasma glucose. However, there was European Scientific Journal November 2017 edition Vol.13, No.33 ISSN: 1857 – 7881 (Print) e - ISSN 1857- 7431 404 no clear association between levels of hs-CRP and the HbA1c, TC, TG, HDL-C, and Apo A1. Conclusion: Measurement of hs-CRP in diabetic patients might provide useful information for development of atherosclerosis and cardiovascular disease and help in early intervention.